“Análisis de la colocación de los microcréditos de la Cooperativa UNIANDES en el mercado mayorista de la ciudad de Riobamba y su influencia en la comercialización del sector periodo julio 2014 a julio 2015”. - Guacho Cajilema, Alex Sebastián (2016)
UNIANDES LTDA credit union began their activities in Nitiliusa Community, Calpi Parish, Riobamba Canton, Chimborazo Province, it began with Community funding or called community funds, through councils seeing the demand and futuristic vision in 2013 is decided to settle in Riobamba city, Condamine neighborhood in Carabobo 10- 21 and Colombia streets, at the second floor for expanding and to be close to one of the crowded and central markets of Riobamba city. To determine the problem and analysis of microcredit is proposed this thesis topic: ANALYSIS OF PLACEMENT MICROLOANS IN UNIANDES CREDIT UNION IN WHOLESALE MARKET IN RIOBAMBA CITY AND ITS INFLUENCE ON THE MARKETING SECTOR PERIOD FROM JULY 2014 TO JULY 2015. This study has the main focus of establishing a detailed analysis through the following types of research, which are: exploratory, descriptive, explanatory. The analysis and guarantees are very important so that it can recover and avoid falling into arrears and nonperforming loans rise. This thesis has 5 Chapters: First Chapter.- This chapter has the frame of reference, it is determined by the problem statement, formulation of the problem, general and specific objectives and the justification. Second Chapter.- It refers to the theoretical framework, it consists in the development of the units of the item, as well as the research hypothesis, variables and operationalization of them. Third Chapter.- This refers to methodological framework based in types of research, sample, survey interpretation and analysts each one. Fourth Chapter.- It consists of conclusions and recommendations which are established at the end of the research. Fifth Chapter.- In this chapter are involved the proposal to develop in UNIANDES credit union, for improving in the placement and monitoring of microcredit, using technological tools, these must be implemented to keep pace with the competition.